Carácter de las ocupaciones humanas en el área de Los Antiguos-Monte Zeballos y Paso Roballos (Santa Cruz, Argentina) - (:unkn) unknown (Utopías, 2009)
This paper explores the dynamics and history of human occupation during the Holocene along the valleys forming a corridor between lake Carrera-Buenos Aires and the Columna-Ghio lakes in N.W. Santa Cruz. The analysis was based on the study of persistent places, those repeatedly used locations as indicated by radiocarbon dates. The intensity of occupation was measured by the abundance (density) of lithic and animal bone discard and the variety of lithic reduction activities. Dated occupations were organized in two chronological periods: a more recent one from 760-1280 cal BP, and an earlier one from 2060-2350 cal BP. The northern Jeinemeni-Zeballos river valley may have been a transit route with relatively short-term stops at strategic places that were recurrently occupied for brief periods. In contrast, the southern Ghio-Columna river valley showed longer-term occupations. This would suggest a different role in mobility with marked differences in the use patterns of places and lithic resources.
VII Jornadas de la Patagonia. Ushuaia, 21-25 abril, 2008
Fil: Mengoni Goñalons, Guillermo L.. Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Arqueología; Argentina.
Fil: Figuerero Torres, María José. Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Arqueología; Argentina.
Fil: Fernández, María Victoria. Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Arqueología; Argentina.
Keywords: Arqueología